2021
DOI: 10.1016/j.ultrasmedbio.2021.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lung Ultrasonography-Guided Management on Cumulative Fluid Balance and Other Clinical Outcomes: A Systematic Review

Abstract: Lung ultrasonography is accurate in detecting pulmonary edema and overcomes most limitations of traditional diagnostic modalities. Whether use of lung ultrasonography-guided management has an effect on cumulative fluid balances and other clinical outcomes remains unclear. In this systematic review, we included 12 studies using ultrasonography guided-management with a total of 2290 patients. Four in-patient studies found a reduced cumulative fluid balance (ranging from À0.3 L to À2.4 L), whereas three out-patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…The methodology and quality assessment tables highlight weaknesses in current lung ultrasound research. Methodological inconsistencies are frequent amongst lung ultrasound investigations, may impact findings, and limit clinical reproducibility or generalizability [ 8 , 9 , 34 ]. The lack of comparator for any of the studies may be intrinsic to the selected outcome, but emphasizes the need for controlled and well-designed studies to study the effect of lung ultrasound beyond clinician behavior: patient-centered and hospital level outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The methodology and quality assessment tables highlight weaknesses in current lung ultrasound research. Methodological inconsistencies are frequent amongst lung ultrasound investigations, may impact findings, and limit clinical reproducibility or generalizability [ 8 , 9 , 34 ]. The lack of comparator for any of the studies may be intrinsic to the selected outcome, but emphasizes the need for controlled and well-designed studies to study the effect of lung ultrasound beyond clinician behavior: patient-centered and hospital level outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cardiac ultrasound requires a high level of expertise along with availability of cardiac windows during suboptimal ICU positioning, decreasing its feasibility. Lung ultrasound, by comparison, requires few examinations to obtain basic proficiency, does not rely on specific thoracic windows, and may readily detect fluid overload as a surrogate for cardiac function (20, 21).…”
Section: Discussionmentioning
confidence: 99%
“…Both negative and positive fluid balance may be associated with increased morbidity and mortality (22). A recent systematic review showed that TUS may facilitate further optimization of volume status (21, 23). This current study’s result emphasizes the important role of TUS in this matter and demonstrates that TUS-guided fluid management induces appropriate and feasible changes in fluid balance that distinctly reflect clinicians’ intent and may not have been produced as readily by the standard diagnostic pathway alone.…”
Section: Discussionmentioning
confidence: 99%
“…Randomised controlled trials (RCT) consistently show that guiding fluid management with LUS is associated with a lower CFB [ 19 ]. In addition, LUS frequently changes patient treatment in the emergency department, ICU and medical ward [ 20 ].…”
Section: Introductionmentioning
confidence: 99%